Emission of nanoparticles from coal and diesel fired power plants on Svalbard: An electron microscopy study. (1st August 2022) - Weinbruch, Stephan; Zou, Linyue; Ebert, Martin; Benker, Nathalie; Drotikova, Tatiana; Kallenborn, Roland
Abstract: Sub-micrometer aerosol particles were collected at the stack of two coal power plants (Barentsburg, Longyearbyen), two diesel power plants (Pyramiden, Sveagruva) and one small-scale coal-burning boiler (Pyramiden) on the Arctic archipelago of Svalbard (Norway). Primary particles (n = 5752) in the size range of 100–1000 nm were investigated by operator-controlled high-resolution scanning electron microscopy (SEM) and energy-dispersive X-ray microanalysis (EDX). Based on morphology and chemical composition primary particles were assigned to one of the following groups: soot, carbonaceous, fly ash spheres, Hg-containing particles, and mineral particles. Soot is the dominating particle group in most samples with a relative number abundance between 69 and 98%. Two coal burning samples have significantly lower soot contents of about 12 and 31%. The relative number abundance of the other particle groups is highly variable. The chemical composition of soot, fly ash spheres and mineral particles was studied in more detail. Soot particles from coal burning are significantly enriched in the elements S, Na, and K compared to diesel soot. The P contents of soot, fly ash spheres, and mineral particles reflect the variable concentration of this element in the different coal seams. Fly ash spheres from coal burning consist of a Si-rich component (quartz or silica glass), alumosilicates or alumosilicate glass, Fe oxides and a Fe, Ca, Al component (most likely a mechanical mixture of spinel and gypsum or lime). Fly ash spheres from diesel burning have a similar composition except that the Fe, Ca, Al component does not occur. Mineral particles from coal burning may be divided into Si-rich (quartz or silica glass), Pb-rich, Fe oxides, alumosilicates or alumosilicate glass and Na-rich particles (most likely a mechanical mixture of Si-rich particles with aged sea salt). The relative number abundance of these subgroups of mineral particles is highly variable. Mineral particles are rare in diesel burning, and seem to be mostly Fe oxides. The observed differences in minor element contents can be used in source apportionment studies for discrimination of individual soot particles as well as fly ash spheres from coal and diesel burning. The highly variable abundance of soot and of mineral particles (especially those consisting predominantly of toxic metals as for example Pb) should be taken into account in exposure assessment. Highlights: Primary nanoparticles emitted from coal power plants are predominantly soot. Number abundance of different groups of nanoparticles is quantified. Soot and fly ash from coal and diesel burning distinguished based on minor elements. Implications for source apportionment of nanoparticles are discussed.